IFNs Modify the Proteome of Legionella-Containing Vacuoles and Restrict Infection Via IRG1-Derived Itaconic Acid. - Jan Naujoks; Christoph Tabeling; Brian D Dill; Christine Hoffmann; Andrew S Brown; Mareike Kunze; Stefan Kempa; Andrea Peter; Hans-Joachim Mollenkopf; Anca Dorhoi; Olivia Kershaw; Achim D Gruber; et al. (PLoS Pathogens)
Macrophages can be niches for bacterial pathogens or antibacterial effector cells depending on the pathogen and signals from the immune system. Here we show that type I and II IFNs are master regulators of gene expression during Legionella pneumophila infection, and activators of an alveolar macrophage-intrinsic immune response that restricts bacterial growth during pneumonia. Quantitative mass spectrometry revealed that both IFNs substantially modify Legionella-containing vacuoles, and comparative analyses reveal distinct subsets of transcriptionally and spatially IFN-regulated proteins. Immune-responsive gene (IRG)1 is induced by IFNs in mitochondria that closely associate with Legionella-containing vacuoles, and mediates production of itaconic acid. This metabolite is bactericidal against intravacuolar L. pneumophila as well as extracellular multidrug-resistant Gram-positive and -negative bacteria. Our study explores the overall role IFNs play in inducing substantial remodeling of bacterial vacuoles and in stimulating production of IRG1-derived itaconic acid which targets intravacuolar pathogens. IRG1 or its product itaconic acid might be therapeutically targetable to fight intracellular and drug-resistant bacteria.